Temperature Anomalies in the Northern and Southern Hemispheres: Evidence of Persistence and Trends - Luis Alberiko Gil-Alana; Nieves Carmona-González (Advances in Meteorology)
This paper analyses temperature anomalies in the northern and southern hemispheres, and the differences between the two in order to estimate the time trend coefficients and the degrees of persistence in the data. Analysing the entire sample period (from 1880m1 to 2022m10), the results indicate lower degrees of persistence and more acute trends in northern hemisphere temperatures. We also observe some degree of persistence and a positive trend for the differenced series. Finally, observing the evolution of these two factors over the last 50 years, we see that in northern temperatures, both the degree of persistence and the time trend have increased over time, whereas similar increases were not observed in southern temperatures.